Spexin-Based Galanin Receptor Type 2 Agonist for Comorbid Mood Disorders and Abnormal Body Weight - Yun, Seongsik; Reyes-Alcaraz, Arfaxad; Lee, Yoo-Na; Yong, Hyo Jeong; Choi, Jeewon; Ham, Byung-Joo; Sohn, Jong-Woo; Kim, Dong-Hoon; Son, Gi Hoon; Kim, Hyun; Kwon, Soon-Gu; Kim, Dong Sik; et al. (Frontiers in Neuroscience, 2019)
Despite the established comorbidity between mood disorders and abnormal eating behaviors, the underlying molecular mechanism and therapeutics remain to be resolved. Here, we show that a spexin-based galanin receptor type 2 agonist (SG2A) simultaneously normalized mood behaviors and body weight in corticosterone pellet-implanted (CORTI) mice, which are underweight and exhibit signs of anhedonia, increased anxiety, and depression. Administration of SG2A into the lateral ventricle produced antidepressive and anxiolytic effects in CORTI mice. Additionally, SG2A led to a recovery of body weight in CORTI mice while it induced significant weight loss in normal mice. In Pavlovian fear-conditioned mice, SG2A decreased contextual and auditory fear memory consolidation but accelerated the extinction of acquired fear memory without altering innate fear and recognition memory. The main action sites of SG2A in the brain may include serotonergic neurons in the dorsal raphe nucleus for mood control, and proopiomelanocortin/corticotropin-releasing hormone neurons in the hypothalamus for appetite and body weight control. Furthermore, intranasal administration of SG2A exerted the same anxiolytic and antidepressant-like effects and decreased food intake and body weight in a dose-dependent manner. Altogether, these results indicate that SG2A holds promise as a clinical treatment for patients with comorbid mood disorders and abnormal appetite/body weight.